Integrating the IBM MQ appliance into your IBM MQ infrastructure - Casey, Neil; Emmett, Andy; Russell, Rufus (IBM Corporation, International Technical Support Organization, 2015)
This IBM® Redbooks® publication describes the IBM MQ Appliance M2000, an application connectivity option that combines secure, reliable IBM MQ messaging with the simplicity and low overall costs of a hardware appliance. This book presents underlying concepts and practical advice for integrating the IBM MQ Appliance M2000 into an IBM MQ infrastructure. Therefore, it is aimed at enterprises that are considering a possible first use of IBM MQ and the IBM MQ Appliance M2000 and those that already identified the appliance as a logical addition to their messaging environment. Details about new functionality and changes in approaches to application messaging are also described. The authors' goal is to help readers make informed design and implementation decisions so that the users can successfully integrate the IBM MQ Appliance M2000 into their environments. A broad understanding of enterprise messaging is required to fully comprehend the details that are provided in this book. Readers are assumed to have at least some familiarity and experience with complimentary IBM messaging products.
Number on resource description page: SG24828300. - Includes bibliographical references. - Description based on online resource; title from cover page (Safari, viewed November 17, 2015)
Keywords: WebSphere; Middleware; Queuing networks (Data transmission); Business enterprises -- Computer networks -- Management; Réseaux de files d'attente (Transmission des données); Entreprises; Réseaux d'ordinateurs; Gestion; Business enterprises; Computer networks; Management